2005
DOI: 10.1016/j.csm.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Training Room Management of Medical Conditions: Infectious Diseases

Abstract: Management of infectious diseases in athletes encompasses a wide range of pathogens, clinical presentations, and treatment options. Certain athletic activities and training regimens may predispose athletes to increased risk of contracting infectious diseases, some of which may limit athletic participation and pose the threat of significant morbidity. The sports medicine physician plays an important role as a first line of defense in preventing, recognizing, and appropriately treating infectious diseases in ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 74 publications
0
31
0
Order By: Relevance
“…15,69,70 Research in the military has demonstrated no significant difference in aerobic capacity and no detrimental effects in those with IM allowed to participate in light exercise ad libitum as soon as they become afebrile, compared with those restricted from activity for 2 weeks. 71 The resumption of light activity assumes that the activity will avoid any chest or abdominal trauma and will not involve significant exertion or Valsalva activities and that the athlete is asymptomatic.…”
Section: Return-to-play Guidelinesmentioning
confidence: 98%
“…15,69,70 Research in the military has demonstrated no significant difference in aerobic capacity and no detrimental effects in those with IM allowed to participate in light exercise ad libitum as soon as they become afebrile, compared with those restricted from activity for 2 weeks. 71 The resumption of light activity assumes that the activity will avoid any chest or abdominal trauma and will not involve significant exertion or Valsalva activities and that the athlete is asymptomatic.…”
Section: Return-to-play Guidelinesmentioning
confidence: 98%
“…Differentiating between aseptic and septic meningitis can be challenging, if not impossible, for the clinician early in the course of the illness. In a clinical series of cases of septic meningitis, only half of patients over 16 yr of age presented with the triad of fever, headache, and meningismus (1,6,23). Given the high rate of mortality and morbidity associated with septic meningitis, a suspected index case of meningitis should be presumed septic until proven otherwise.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The close physical contact, close living, and traveling arrangements associated with many team sports are thought to increase the transmissibility of infectious pathogens (1).…”
Section: Introductionmentioning
confidence: 99%
“…URTI affects almost every healthy adult one to six times a year, is probably the most common infection seen in the training room, and predominates among participants at the Olympic Games (19). URTI generally is viral and transmitted by direct contact, usually hand to nose, eyes or mouth, small particle aerosols, and large particle droplets.…”
Section: Urtimentioning
confidence: 99%
“…Infectious mononucleosis (EBV) pharyngitis may present with URTI symptoms and swollen, erythematous tonsils with exudate, palatal petechial, and splenomegaly. Rapid strep screening tests are up to 80% to 90% sensitive in diagnosing strep throat (19). The modified Centor Score is a clinical decision rule that can aid in management of pharyngitis (10).…”
Section: Pharyngitismentioning
confidence: 99%